Examining the effectiveness of a nationwide place-based policy approach to improving physical activity participation: a controlled interrupted time series analysis - Andrew Brinkley; Paul Freeman (Journal of Public Health, 2026)
Abstract Aim Physical inactivity is a persistent public health challenge in England, linked to non-communicable diseases, poor mental health, and health inequalities. Therefore, in 2016, Sport England launched 12 local delivery pilots (LDPs) as part of the ‘Towards an Active Nation’ strategy. These aimed to reduce inactivity through whole-systems and place-based approaches. Despite extensive process evaluation, little is known on the population-level impact of these programmes on physical activity participation. Subject and methods To understand this, we utilised controlled interrupted time series analysis using Active Lives Survey data from 2015 to 2023 ( n = 1,437,748 adults) to examine the impact of LDPs on moderate equivalent minutes (MEMs) of physical activity. We compared trends in LDP areas against location-based control areas (non-LDP areas) and examined variation between individual LDPs. Results Analysis revealed that MEMs were declining in LDP areas during baseline ( β = −1.16 min/month, p = 0.005). Following LDP implementation, this decline slowed ( β = +0.61, p = 0.051), and reversed post-funding ( β = +1.16, p = 0.051). However, when accounting for control areas, analysis demonstrated no statistically meaningful differences between LDP and control trajectories during implementation ( β = −0.94, p = 0.29), post-LDP ( β = −0.85, p = 0.58), or COVID-19 periods ( β = −0.29, p = 0.81). Analysis of individual LDPs similarly showed no significant improvements in MEMs compared with controls. Conclusion The lack of improvement may be due to the focus on ‘downstream’ leverage points and time delays inherent in systems-change approaches. Moreover, for whole-systems approaches to be successful, there is a need for sustained implementation, shared commitment, and a focus on ‘upstream’ leverage points.